2020
DOI: 10.1001/jamanetworkopen.2020.6004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Care Exposures and Outcomes in Adult Patients With Sepsis and Septic Shock

Abstract: IMPORTANCECurrent information on the characteristics of patients who develop sepsis may help in identifying opportunities to improve outcomes. Most recent studies of sepsis epidemiology have focused on changes in incidence or have used administrative data sets that provided limited patientlevel data. OBJECTIVE To describe sepsis epidemiology in adults. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study reviewed the medical records, death certificates, and hospital discharge data of adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 16 publications
(34 reference statements)
2
40
0
1
Order By: Relevance
“…Similar to other studies, a higher incidence was observed for males compared with females, for very young infants or elderly, and for patients with comorbidities 13 23 30–33. Indeed, ageing is associated with increased prevalence of chronic diseases and impaired immune system, thus increasing the risk of sepsis 32.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to other studies, a higher incidence was observed for males compared with females, for very young infants or elderly, and for patients with comorbidities 13 23 30–33. Indeed, ageing is associated with increased prevalence of chronic diseases and impaired immune system, thus increasing the risk of sepsis 32.…”
Section: Discussionsupporting
confidence: 83%
“…Other notable findings we observed in our review of included studies that were not reported consistently or easily quantified are summarized in Table 1 . Of the two studies investigating antibiotic use prior to admission, antibiotic use was noted to increase in the days leading up to a sepsis hospitalization and up to 73.4% of patients had received antibiotics in the 30 days prior ( 9 , 16 ). Documentation of infectious disease diagnoses or symptoms ranged from 27.0% to 80.5% ( 16 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that 80% of hospitalized patients with sepsis present from the community setting ( 9 , 10 ), patient encounters with the healthcare system in the week(s) prior to a sepsis hospitalization (prehospital encounters) represent opportunities for early identification of the transition from infection to sepsis, more intensive monitoring in certain patients, and potential opportunities for intervention to reverse course. Estimating the overall proportion of patients with a prehospital “touch point,” along with information about the healthcare setting and resulting clinical outcomes, is critical to inform potential interventions.…”
mentioning
confidence: 99%
“…The patients' electronic or paper medical files were consistently reviewed for 4 calendar days or until discharge from the hospital. The primary endpoint of this study was the diagnosis of sepsis within 96 h. Our aim was to include all patients with communityacquired sepsis, since these are the most common ones [29,30] and usually present to EDs in need of early sepsis management [31]. Furthermore, the board of the clinical trial aimed to include late sepsis development so that early biomarker diagnostic performance could be assessed.…”
Section: Endpointsmentioning
confidence: 99%